2003
DOI: 10.1093/toxsci/kfg202
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor 2 Mediates 2,3,7,8-Tetrachlorodibenzo-p-dioxin Developmental Toxicity in Zebrafish

Abstract: In order to use the zebrafish as a model vertebrate to investigate the developmental toxicity of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), it is essential to know whether one or both forms of the zebrafish aryl hydrocarbon receptor (AHR), zfAHR1 or zfAHR2, mediate toxicity. To determine the role of zfAHR2, an antisense morpholino approach was used to knock down translation of the protein. No effect of the zfahr2 morpholino (zfahr2-MO) was seen on normal development in embryos not treated with TCDD. Injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
217
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(233 citation statements)
references
References 43 publications
14
217
2
Order By: Relevance
“…Previous studies have reported the AHR-mediated induction of CYP1A expression by various environmental pollutants (e.g., PAHs) in fish (Prasch et al, 2003;Timme-Laragy et al, 2007). Pyrene is considered to be a weak AHR agonist (Barron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the AHR-mediated induction of CYP1A expression by various environmental pollutants (e.g., PAHs) in fish (Prasch et al, 2003;Timme-Laragy et al, 2007). Pyrene is considered to be a weak AHR agonist (Barron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…AHR activation during embryonic development leads to altered gene expression, malformations, and decreased survivorship (Billiard, Meyer, Wassenberg, Hodson, & Di Giulio, 2008; King‐Heiden et al., 2012). Experimental knockout or knockdown of AHR function protects against HAH‐ and PAH‐induced toxicity (Billiard, Timme‐Laragy, Wassenberg, Cockman, & Di Giulio, 2006; Clark, Matson, Jung, & Di Giulio, 2010; Fernandez‐Salguero, Hilbert, Rudikoff, Ward, & Gonzalez, 1996; Goodale et al., 2012; Incardona, Day, Collier, & Scholz, 2006; Incardona et al., 2005; Jönsson, Jenny, Woodin, Hahn, & Stegeman, 2007; Prasch et al., 2003); thus, evolved desensitization of this signaling pathway is plausibly causative for adaptive pollutant tolerance in killifish.…”
Section: Nature Of Parallel Pollution Adaptation In Killifishmentioning
confidence: 99%
“…However, sustained activation of AHR, such as occurs by exposure to poorly metabolizable DLCs or constant exposure to labile AHR agonists, leads to toxicity through sustained misregulation of genes involved in cellular homeostasis. The AHR is thus an integral component of the mechanism by which DLCs and some PAHs cause toxicity, and loss of AHR function protects against these effects (Fernandez‐Salguero et al., 1996; Goodale et al., 2012; Mimura et al., 1997; Prasch et al., 2003). Although the AHR is now known to participate in a variety of additional, noncanonical interactions and pathways (Jackson, Joshi, & Elferink, 2015), the primary mechanism of toxicity appears to involve canonical interactions requiring nuclear localization, dimerization with ARNT, and binding to AHREs (Bunger et al., 2003, 2008; Nukaya, Walisser, Moran, Kennedy, & Bradfield, 2010; Walisser, Bunger, Glover, Harstad, & Bradfield, 2004).…”
Section: Ahr Pathwaymentioning
confidence: 99%
See 2 more Smart Citations